Intermatch variation of match activity in elite Italian soccer referees - Castagna, C.; Abt, G. (The Journal of Strength and Conditioning Research, 2003)
The aim of this study was to examine how match activities, specifically high-intensity activity (HIA; activities performed at speeds faster than 18.1 km·h1), vary among matches in elite soccer referees, because variations in match performance can potentially guide physical conditioning regimens for these referees. Fourteen Italian soccer referees were observed during 65 first-division matches a minimum of 3 and a maximum of 6 times each. For comparison, shorter matches (SM) and longer matches (LM) for each referee were identified. Mean (±SD) SM and LM total distances were 10,949 ± 1,095 m and 12,303 ± 666 m (p < 0.001), respectively. SM and LM were not different in term of duration (p > 0.05). During LM, referees spent 44% less time standing still (p < 0.01) and covered 10% more distance at low intensity than they did in SM (p < 0.05). No HIA variation was observed between SM and LM (p > 0.05). For the elite referee, work rate is increased without affecting HIA.